DAMPAK KOMPENSASI DAN PENERAPAN KESELAMATAN KESEHATAN KERJA (K3) PADA KINERJA KARYAWAN PT. XYZ - Della Ayu Minarni; Kustini Kustini (Universitas Sarjanawiyata Tamansiswa, 2025)
This research aims to examine the influence of compensation and the implementation of occupational health and safety (K3) on employee performance at PT. XYZ. This study employed a quantitative approach, with a population and sample size of 52 production employees. Primary data were collected through the distribution of questionnaires to employees in the production department. The data analysis approach used was Partial Least Squares (PLS). The research findings confirm that compensation and the implementation of OHS have a positive and significant impact on employee performance. This suggests that strengthening the compensation system and implementing OHS consistently and firmly can spur improvements in overall employee performance.